Cyanogen: A Versatile Reagent for Diversity-Oriented Synthesis - Polák, Peter; Dvořák, Dalimil; Tobrman, Tomáš (Synthesis, 2017)
This short review summarises the synthetic applications of cyanogen. The review is divided into several parts, including transition-metal-catalysed reactions, addition reactions, and cyclisation processes.1 Introduction2 Addition Reactions3 Ring-Closure Reactions4 Transition-Metal-Catalysed Reactions5 Conclusions
Keywords: cyclization; cycloaddition; heterocycles; transition metals; addition